Personal digital repository using greenstone - Ab Rahman, Azmi; Endin, Mohd Zailan; Othman, Ahmad Soufiean; Abdul Rahman, Abdul Rashid; Md Eusoff, Ahmed Noor Kader Mustajir (Universiti Teknologi MARA, Kedah, 2018)
Contribution of personal performance toward preservation of cultural heritage is a vital one. There is a lacuna of preservation this type of material in digital format which lead to the difficulties in accessing and preserving this material. This study aims to demonstrate that digital repositories are important for the storage, description, access and preservation of personal document and information. Greenstone software and Dublin Core Standard were used in this study. It is hope that the implementation of personal digital repository will bring forward the importance of preservation, access and sharing of personal documents and resources produced by individuals in the digital era. This project is unique due to it focus on the individual/personal documents and resources